Inward-rectifier chloride currents in Reissner’s membrane epithelial cells - Kim, Kyunghee (Kansas State University, 2010)
Sensory transduction in the cochlea depends on regulated ion secretion and absorption. Results of whole-organ experiments suggested that Reissner’s membrane may play a role in the control of luminal Cl-. We tested for the presence of Cl- transport pathways in isolated mouse Reissner’s membrane using whole-cell patch clamp recordings and gene transcript analyses using RT-PCR. The current-voltage (I-V) relationship in the presence of symmetrical NMDG-Cl was strongly inward-rectifying at negative voltages, with a small outward current at positive voltages. The inward-rectifying component of the I-V curve had several properties similar to those of the ClC-2 Cl- channel. It was stimulated by extracellular acidity and inhibited by extracellular Cd2+, Zn2+, and intracellular ClC-2 antibody. Channel transcripts expressed in Reissner’s membrane include ClC-2, Slc26a7 and ClC-Ka, but not Cftr, ClC-1, ClCa1, ClCa2, ClCa3, ClCa4, Slc26a9, ClC-Kb, Best1, Best2, Best3 or the beta-subunit of ClC-K, barttin. ClC-2 is the only molecularly-identified channel present that is a strong inward rectifier. This thesis incorporates the publication by K.X. Kim and D.C. Marcus, Inward-rectifier chloride currents in Reissner’s membrane epithelial cells. Biochem. Biophys. Res. Commun. 394 (2010) 434-438, with permission of the publisher Elsevier, and is the first report of conductive Cl- transport in epithelial cells of Reissner’s membrane and is consistent with an important role in endolymph anion homeostasis.
Keywords: Cl- channel; Epithelial transport; Cochlea; ClC-2 channel; Biology, Veterinary Science (0778)